Agrobacterium tumefaciens VirB9, an Outer-Membrane-Associated Component of a Type IV Secretion System, Regulates Substrate Selection and T-Pilus Biogenesis - Jakubowski, Simon J. (American Society for Microbiology, 2005)
Agrobacterium tumefaciens translocates DNA and protein substrates between cells via a type IV secretion system (T4SS) whose channel subunits include the VirD4 coupling protein, VirB11 ATPase, VirB6, VirB8, VirB2, and VirB9. In this study, we used linker insertion mutagenesis to characterize the contribution of the outer-membrane-associated VirB9 to assembly and function of the VirB/D4 T4SS. Twenty-five dipeptide insertion mutations were classified as permissive for intercellular substrate transfer (Tra(+)), completely transfer defective (Tra(−)), or substrate discriminating, e.g., selectively permissive for transfer only of the oncogenic transfer DNA and the VirE2 protein substrates or of a mobilizable IncQ plasmid substrate. Mutations inhibiting transfer of DNA substrates did not affect formation of close contacts of the substrate with inner membrane channel subunits but blocked formation of contacts with the VirB2 and VirB9 channel subunits, which is indicative of a defect in assembly or function of the distal portion of the secretion channel. Several mutations in the N- and C-terminal regions disrupted VirB9 complex formation with the outer-membrane-associated lipoprotein VirB7 or the inner membrane energy sensor VirB10. Several VirB9.i2-producing Tra(+) strains failed to elaborate T pilus at detectable levels (Pil(−)), and three such Tra(+) Pil(−) mutant strains were rendered Tra(−) upon deletion of virB2, indicating that the cellular form of pilin protein is essential for substrate translocation. Our findings, together with computer-based analyses, support a model in which distinct domains of VirB9 contribute to substrate selection and translocation, establishment of channel subunit contacts, and T-pilus biogenesis.